West African irrigation and drainage association - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Until recently, the West African irrigation community has had low representation in the activities of the International Commission on Irrigation and Drainage (ICID). Nigeria and Senegal were the only two countries with active local committees....